Characterization and properties of transparent cellulose nanowhiskers-based graphene nanoplatelets/multi-walled carbon nanotubes films. (July 2016) - Liu, Yueyue; Liu, Dongyan; Ma, Yuling; Sui, Guoxin
Abstract: Transparent cellulose nanowhiskers (CNW)/graphene (GN) and CNW/multi-wall carbon nanotube (MWCNT) films were obtained by ultrasonication assisted mechanically stirring followed by solvent casting methods. GN has more significant influence on the properties of CNW film than MWCNT does because GN exhibits strong interaction with CNW by its adsorption on the surface of GN. Thermal behaviors of CNW-based composite films were greatly affected by addition of GN or MWCNT. The melting peak and initial degradation temperature increase by 23.5 and 24 °C, and by 78 °C and 94 °C for the composite films containing 5 wt% MWCNT and 5 wt% GN, respectively. The composites show the contact angles of 61.9° for GN included film and 46.9° for MWCNT included film, which is higher than that of pure CNW film (42.8°).